Ethnic Mobilisation in Politics - Machangana Ruling Over (Journal of Namibian Studies : History Politics Culture, 2023)
"Ethnic Mobilisation in Politics - Machangana Ruling Over" is an article that composes a chapter of the ongoing Thesis entitled "The Influence of Ethnicities in Political Conflicts in African States: The Case Study of Mozambique (1976-2019)". It aims to analyse ethnic mobilisation to political support as a potential influencer to the emergence of political conflicts in Mozambique. The main conclusion shows that in Mozambique there is a strong ethnic support to politics, in such a way that each presidential candidate and his Political party have its bastion in his ethnic origin. However, it is not a result of an ethnic mobilisation, but in a scarcity of political records, the voters scrutinise the candidate based on the easiest information available, which is ethnicity. The article reviews the role of ethnicities in South Africa and Angola to be used as a brief comparison with Mozambique, from which concluded that, the more ethnicities play an important role in politics, the country is likely vulnerable to political conflicts. The study is a result of a field research conducted via interviews, during 45 days of a participant observation in Mozambique.